Allergic history and responses to immunotherapy in individuals with recurrent or metastatic head and neck squamous cell carcinoma - Wang, Yannan; Ma, Zhonghui; Zheng, Qizhe; Chu, Yinglin; Hu, Yunshuang; Liu, Fei (Frontiers in Oncology, 2025)
ObjectiveTo elucidate the association between allergy history and response to immune checkpoint inhibition (ICI) in recurrent or metastatic head and neck squamous cell carcinoma (RM/HNSCC).MethodsPatients receiving ICI treatment for RM/HNSCC were retrospectively enrolled and classified into two groups based on their previous allergy history. The primary outcome variable assessed was the response to ICI.ResultsA total of 157 patients were included, of whom 27 reported a history of allergies. In multivariate analysis, patients with allergies exhibited an odds ratio of 2.78 [95% confidence interval: 1.54-5.99], significantly surpassing that of the non-allergic group. Other independent predictors of ICI benefit included current smoking status and the primary tumor site being in the oropharynx or hypopharynx. Neither progression-free survival nor overall survival was adversely affected by prior allergy history or smoking status or HPV status or PD-L1 expression.ConclusionA prior history of allergies is associated with an enhanced response to immunotherapy in patients with RM/HNSCC.